Wykonywanie zadań publicznych przez muzea jako przesłanka wyłączenia ochrony prawnoautorskiej informacji o zasobach publikowanych w Internecie - Drela, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The current key problem associated with access to culture is to adapt existing legislation to a new area of social life, i.e. Internet and the possibilities it offers: simple dissemination of information among the people. This problem also affected museums which in the new reality are forced to carry out their tasks using a new tool — the Internet. A large part of exhibits in public museums collections is subject to both regulations: public sector information and the copyright protection, where the third party not a museum is also entitled to copyrights. In the Polish legislative body, works are undertaken in order to implement the Directive of the European Parliament and of the Council 2013/37 / EU of 26 June 2013, amending Directive 2003/98 /EC on the re-use of public sector information i.e. the Directive re-use, ordering to share resources located in museums. In this paper the author’s aim is to analyze Art. 4 item 2 of the Polish Copyright Law in the context of exercising public tasks by public museums in the process of digitizing and making available online digitized collections. It is important to determine to what extent the current legal situation de lege lata allows to freely dispose of digital content created in the process of digitization by public museums. According to Art. 4 of the Polish Copyright Law the following are not subject to copyright: 1 legislative acts and their official drafts; 2 official documents, materials, signs and symbols; 3 published patent or protection; 4 simple press releases. In the opinion of the author, the content of point 2 of that Article allows to make a statement that database produced by public museum in the process of digitization of their possessions is designate of the term “official material” referred to in Art. 4 point 2 of copyright law, which allows free access to public databases online.
Keywords: public tasks; museums; internet; Polish copyright law; datebase